Strategies for economic development in Brazil: A Structuralist-Keynesian approach - de Paula, Luiz Fernando; Oreiro, José Luis (PSL Quarterly Review, 2025)
This paper aims to analyze the main reasons to the tendency toward stagnation of the Brazilian economy and to discuss a strategy of sustained development to overcome such tendency from a Keynesian-Structuralist approach, more specifically adopting a New-developmentalism green agenda. A sustained development strategy requires the reconstruction of the manufacturing industry not only to meet domestic demand but to conquer a larger and increasing share of world manufacturing exports. This goal has to be accomplished side by side with a sustainable environmental agenda, aimed at decarbonization and accelerating change in the environment.